Obesity and Male Infertility: A Practical Approach - Hammoud, Ahmad O.; Meikle, A. Wayne; Reis, Leonardo Oliveira; Gibson, Mark; Peterson, C. Matthew; Carrell, Douglas T. (Seminars in Reproductive Medicine, 2012)
Obesity in men is associated with infertility in numerous studies, and the temporal trend for a decline in semen parameters parallels the increasing prevalence of obesity in the developed world. In addition to impaired semen quality, fertility among obese men may be affected by decreased libido and erectile dysfunction. This spectrum of expression of hypogonadism among obese men originates from multiple interacting factors including reduced levels of gonadotropins and testosterone, altered androgen-to-estrogen ratios, insulin resistance, and sleep apnea. No evidence-based treatment that increases the likelihood of pregnancy for the infertility associated with male obesity has been demonstrated to date. Interventions associated with improvement of intermediate outcomes that include the endocrine profile, semen parameters, and sexual function may be appropriately selected based on history, physical findings, as well as endocrine and metabolic evaluation. Among these interventions are weight loss through lifestyle change, relief from sleep apnea, use of aromatase inhibitors, gonadotropin administration, phosphodiesterase inhibitors, and insulin-sensitizing agents.
Keywords: male infertility; overweight; BMI; semen parameters; treatment; reproductive function